2019
DOI: 10.1037/pas0000756
|View full text |Cite
|
Sign up to set email alerts
|

Postconcussive, posttraumatic stress and depressive symptoms in recently deployed U.S. Army soldiers with traumatic brain injury.

Abstract: Prior studies raise questions about whether persistent postconcussive symptoms (PCS) are differentiable from mental health sequelae of traumatic brain injury (TBI). To investigate whether PCS represented a distinct symptom domain, we evaluated the structure of post-concussive and psychological symptoms using data from The Army STARRS Pre/Post Deployment Study, a panel survey of three U.S. Army Brigade Combat Teams that deployed to Afghanistan. Data from 1229 participants who sustained probable TBI during deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 58 publications
(85 reference statements)
1
17
0
Order By: Relevance
“…The two anxiety studies utilized two different measures; the anxiety item bank from the Quality of Life in Neurological Disorder Computerized Adaptive Tests ( 60 , 92 ), and the Hospital and Anxiety Depression Scale ( 12 , 93 ). The eight adult studies that centered on symptoms of depression utilized the adapted version of the Composite International Diagnostic Interview Screening Scales ( 61 , 88 ), qualitative interviews ( 62 , 81 ), the British Columbia Major Depression Inventory, 2nd Edition ( 63 , 82 ), the Center for Epidemiological Studies Depression Scale ( 64 , 83 ), the Beck Depression Inventory ( 65 , 66 , 68 , 94 ), or the General Health Questionnaire ( 67 , 84 ). Between the nine adult studies on combined symptoms of anxiety and depression, four used the Hospital Anxiety and Depression Scale ( 70 , 72 , 75 , 76 , 93 ), while others used the Impact of Event Scale ( 69 , 95 ), the Rivermead Post-Concussion Symptoms Questionnaire ( 69 , 96 ), Depression and Anxiety Stress Scales-42 ( 71 , 85 ), the Beck Anxiety Inventory ( 73 , 86 ) and Beck Depression Inventory ( 73 , 94 ), interviews with symptoms according to DSM-IV criteria ( 74 , 87 ), and the Glasgow Outcome Scale -Extended ( 77 , 97 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two anxiety studies utilized two different measures; the anxiety item bank from the Quality of Life in Neurological Disorder Computerized Adaptive Tests ( 60 , 92 ), and the Hospital and Anxiety Depression Scale ( 12 , 93 ). The eight adult studies that centered on symptoms of depression utilized the adapted version of the Composite International Diagnostic Interview Screening Scales ( 61 , 88 ), qualitative interviews ( 62 , 81 ), the British Columbia Major Depression Inventory, 2nd Edition ( 63 , 82 ), the Center for Epidemiological Studies Depression Scale ( 64 , 83 ), the Beck Depression Inventory ( 65 , 66 , 68 , 94 ), or the General Health Questionnaire ( 67 , 84 ). Between the nine adult studies on combined symptoms of anxiety and depression, four used the Hospital Anxiety and Depression Scale ( 70 , 72 , 75 , 76 , 93 ), while others used the Impact of Event Scale ( 69 , 95 ), the Rivermead Post-Concussion Symptoms Questionnaire ( 69 , 96 ), Depression and Anxiety Stress Scales-42 ( 71 , 85 ), the Beck Anxiety Inventory ( 73 , 86 ) and Beck Depression Inventory ( 73 , 94 ), interviews with symptoms according to DSM-IV criteria ( 74 , 87 ), and the Glasgow Outcome Scale -Extended ( 77 , 97 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 studies that centered around adults with PPCS, eight studies measured symptoms of depression ( 61 68 ). Like in the pediatric population, most studies found that participants reporting higher PPCS symptoms also reported higher severity of depression symptoms ( 64 , 65 , 67 , 68 , 82 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 As such, postconcussive (PCS) and posttraumatic stress (PTS) symptoms are often studied together among military service members. 2,[13][14][15]…”
Section: Symptoms Of Mtbi and Related Conditions Among Military Servi...mentioning
confidence: 99%
“…Estimates of TBI among service members who have returned from military operations in Iraq and Afghanistan vary moderately, which highlights the critical importance of TBI definitions and methods to ascertain TBI exposure. Estimates suggest that between 9% and 28% of service members experienced a TBI . Complicating matters further, many veterans experienced 1 or more TBIs before their military service, thereby suggesting that military-related injuries may be neither the first nor the worst lifetime injury sustained.…”
mentioning
confidence: 99%